Molecular Diagnosis of Duchenne/Becker muscular dystrophy in a family with no pathological antecedents of the disease - Ivonne Martín Hernández; Alejandro Ariosa Olea; Mariesky Zayas Guillot; Tatiana Zaldívar Vaillant; Celia Rosa Soto Pérez-Stable (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2018)
Foundation: Duchenne and  Becker muscular dystrophies are progressive neuromuscular diseases with a pattern of recessive inherited link to chromosome X and caused by mutations in the gene which codifies for dystrophin. The study of possible carriers in affected families is crucial since it generates expectations and options on genetic advisory. Objective: to describe the molecular diagnosis of Duchenne/Becker muscular dystrophy  in a family without pathological antecedents of the disease. Methods: an experimental study was developed about the deletions of Duchenne/Becker gene of muscular dystrophy, in a patient with clinical diagnosis of the disease. It was used multiple PCR technique following the methods described by Beggs and Chamberlain. In addition, the women of the family were studied by the analysis of polymorphic markers through short repetitions in (CA) n tandem. Results: deletions of exons from 47 to 52 were identified in the patient; so as the precedence of the X chromosome related to the disease (maternal grandfather). It was determined the state of non-carrier in three women of the family. It was not possible to exclude germline mosaicism in the child´s mother. Conclusion: the occurrence of a novo mutation was inferred. The molecular diagnosis allowed confirming the diagnosis of the affected child; in addition it was possible to offer adequate genetic advisory to the family.